The relationship between workers' financial participation in companies and economic results - Maciej Kozłowski (Comparative Economic Research. Central and Eastern Europe, 2014)
It is known that workers' financial participation, primarily in the form of wider participation of employees in profits and ownership, has been used in enterprises from many years, but in practice the period of implementation of different forms of financial participation has taken place only in the last four decades. Workers' participation in decision-making has a longer tradition, so it is well described in the literature, and its impact on the results achieved by companies are known through the many research projects conducted by researchers around the world and through detailed reports. Financial participation has not been the focus of so many papers, so the knowledge and information from this area is incomplete. This is because of the lack of comprehensive studies on the various forms of participation, their irregularity, the lack of cooperation between states in the exchange of information concerning the number of implemented solutions, etc. Of course, it is not possible to include all of the companies in research and the results cannot be generalized due to the different conditions and selection criteria in particular countries. Also, the ambiguous interpretation of the term "financial participation" by different authors and different institutions does not allow for setting up and developing the output database necessary to conduct the research and carry out comparisons. In the literature, programs of financial participation are treated as an incentive system, without taking into account the wider context and the relationships between these programmes and the results achieved by the company. This contribution aims to give some theoretical and scientific examples, which, by virtue of their nature and severity can contribute to the possible diverse research solutions to the problems facing businesses, especially in today's dynamic, global economy. After forty years of empirical research on the benefits of the implementation of various programmes of financial participation, the information provided, in principle, only in the form of reports, is not sufficient to express opinions on the development of forms of participation. At the same time, it is concluded that the programmes of financial participation have had a positive effect on the results achieved by companies, especially in terms of social benefits. Arriving at the above opinion has been additionally impeded by the different attitudes of the social partners to the issue of participation and participatory approaches, the absence of explicit data showing the relationship between implemented financial schemes and financial results, changes in the competitive position of enterprises, etc. The outlined theory concerning how the workers' ownership affects economic performance achieved by a company unfortunately has not changed. This article is not to bring about fundamental changes, but to find new threads or directions of deliberation.
Keywords: 330; financial participation; profit sharing; Workers' ownership; workers' attitudes